Selenium status and tryptophan catabolites as predictive biomarkers of depression in hypothyroid patients - Al-Baldawi, S. Q.; Al-Hakeim, H. K.; Khémiri, I. (Regulatory Mechanisms in Biosystems, 2025)
Depression is a common comorbidity among patients with hypothyroidism (HT) and is closely associated with alterations in various biological pathways. Among these, selenium (Se), selenoprotein-P (SEPP), and tryptophan catabolites (TRYCATs) have emerged as potential biomarkers. This study aimed to evaluate the predictive role of Se, SEPP, and TRYCATs in identifying depression among hypothyroid patients. A case-control study was conducted on 120 hypothyroid patients, subdivided into two groups: 60 patients with depression (HT+Depression) and 60 without depression (HT only). Additionally, 60 age- and sex-matched healthy individuals served as controls. Serum Se levels were determined using flameless atomic absorption spectroph o tometry, while SEPP and TRYCATs, including kynurenic acid (KYNA), 3-hydroxykynurenine (3HK), and quinolinic acid (QA), were quantified via ELISA. The Hamilton Depression Rating Scale (HAM-D) was used to assess depression severity. Statistical analyses included ANOVA, ROC curves, and principal component analysis. Patients in the HT+Depression group exhibited significantly lower levels of SEPP, KYNA, 3HK, and QA/KYNA compared to both the HT-only and control groups. KYNA emerged as the strongest predictor of depression, with a cut-off value of 26.18 nM (Youden’s J = 0.634, AUC = 0.89). Principal component analysis demonstrated strong correlations between thyroid biomarkers, TRYCATs, and depression severity. Depression in hypothyroid patients is strongly associated with alterations in Se, SEPP, and TRYCATs. Among these, KYNA shows the highest diagnostic accuracy and may serve as a reliable predictive biomarker for depression in hypothyroidism.